Hubungan Ketersediaan Tanah dengan Kawasan Siap Bangun dan Lingkungan Siap Bangun dalam Pembangunan Kota Baru Manado (Studi di Kecamatan Mapanget Kota Manado Provinsi Sulawesi Utara) - Try Saut Martua Siahaan; Sutaryono Sutaryono; Westi Utami (Tunas Agraria, 2019)
Abstract: The high flow of urbanization and uneven population growth, led to the plan to move the downtown of Kota Baru Manado to Mapanget Sub-district. The Planning of development for Ready To Build Area (Kasiba) and Ready to Build Environment (Lisiba) is carried out by considering the potential of each region so creating an integrated Kasiba and Lisiba development. The research method that used was descriptive qualitative method with spatial approach. The method of analysis that conducted in this study was spatial analysis method with overlay technique that used GIS technology. Spatial analysis with overlay technique is a process of analyzing and integrating two or more different spatial data to obtain new spatial data. The overlay technique was implemented based on the integration model between the Kasiba and Lisiba Potential Region Map with the Kota Baru Manado’s Land Availability Scale.Based on the research results could be seen that in the framework of preparation of Kasiba and Lisiba, Land Stewardship Scale provided the information of the use and control of land, the suitability of land use with RTRW and the availability of land. More than half of MapangetSub-district entered into the permitted land use zone and the remainder included into a limited/conditional permitted land use zone with a 59%: 41% ratio.Keywords: land availability, kasiba and lisiba, Kota Baru ManadoIntisari: Tingginya arus urbanisasi dan pertumbuhan penduduk yang tidak rata menyebabkan adanya rencana untuk memindahkan pusat Kota Baru Manado ke Kecamatan Mapanget. Perencanaan pembangunan Kawasan Siap Bangun (Kasiba) dan Lingkungan Siap Bangun (Lisiba) dilaksanakan dengan memperhatikan potensi masing-masing daerah sehingga mewujudkan suatu pembangunan Kasiba dan Lisiba yang terpadu. Metode penelitian yang digunakan adalah metode deskriptif kualitatif dengan pendekatan keruangan (spatial approach). Metode analisis yang dilakukan dalam penelitian ini menggunakan metode analisis spasial dengan teknik tumpang susun (overlay) menggunakan teknologi SIG. Hasil penelitian menunjukkan dalam penyusunan Kasiba dan Lisiba, Neraca Penatagunaan Tanah memberikan informasi mengenai penggunaan dan penguasaan tanah, kesesuaian penggunaan tanah dengan RTRW serta ketersediaan tanah. Ketersediaan tanah untuk pembangunan berkelanjutan harus memperhatikan penggunaan, penguasaan, kemampuan tanah serta kerawanan terhadap bencana.Kata Kunci: ketersediaan tanah, kasiba dan lisiba, Kota Baru Manado